Determining counselors' spontaneous attention to verbal utterances and exploring perceptions on effective counselor-client communication - Lopez, Jomelyn Gomez (Animo Repository, 2018)
To determine Filipino counselors’ spontaneous attention to verbal utterances (vocal tone versus verbal content), and counselors’ and student-clients’ perceptions on effective counselor-client communication, two concurrent studies were conducted in this research. Study 1 was a mixed-method explanatory sequential study that determined Filipino counselors’ spontaneous attention to verbal utterances either focusing more on verbal content or vocal tone. The quantitative phase of Study 1, with a sample of 80 counselors, utilized a 2 x 2 (Task x Type of Stimulus) mixed between-within subjects experimental design. The results showed a significant interaction effect between Task (Verbal-Content Meaning Judgment vs. Vocal-Tone Meaning Judgment) and Type of Stimulus (Congruous vs. Incongruous), with (F(1, 78) = 4.191, p = .05. Significant main effects were also found due to Task (F(1,78) = 4.066, p = 0.05, and Type of Stimulus (F(1,78) =19.193, p = 0.001. The qualitative phase involving 30 counselors further elaborated the results gained from the experiment revealing the factors for the longer response time in judging the meaning of verbal content with incongruous stimuli and the factors for the shorter response time in judging the meaning of vocal tone with incongruous stimuli showing a strong attentional bias for vocal tone. Specific themes which operated within the Filipino counselors’ experiences were also identified. In Study 2, 20 counselors and 30 student-clients participated in a qualitative study to explore perceptions on effective counselor-client communication. Results revealed that counselors’ and student-clients’ perceptions on effective counselor-client communication reveals primacy of words and content over contextual elements. Results of Study 2 showing words and content as deemed important components in effective counselor-client communication are not consistent with the results of Study 1 revealing spontaneous attentional bias for vocal tone. Implications for the counseling practice, counselor training, and future research were discussed.